CREATIVITY AND COLLABORATION EMPLOYED BY ENGLISH DEPARTMENT STUDENTS IN DEVELOPING LEARNING MEDIA (RETAIN, 2020)
Creativity and collaboration are known as one of learning objective in today’s teaching and learning process. However, creativity and collaboration have not been highly promoted in students’ activities in developing learning media. Regarding that there are many people, especially English teachers and students, in Indonesia who have not been aware of how developing learning media contributes in the development of creativity and collaboration, this research is aimed to focus on describing the creativity and collaboration of the sixth semester students of English department in developing their learning media. The base of this research is using descriptive qualitative as research design. The data were gained through observations and interview. The result of this study figure out that most of students are demanded to think creatively and collaborate in developing learning media. Combination of ideas from various sources, understanding of the material, problem solving and the use of learning media itself were creativity indicators that always appears in developing learning media. While discussion, sharing task and help each other are prominent collaboration indicators in developing learning media. In addition, the results of this study stated that by giving assignments to develop learning media, students are greatly helped in practicing creativity and collaboration and have a better understanding of the material.